(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Substance abuse is a critical problem among adolescents and young adults in lead-city university, Ibadan, Oyo State, Nigeria, yet empirical evidence on substance use is limited. This study explored the knowledge, attitude, and perceptions of drug abuse among undergraduate of a university in Southwest Nigeria to help develop a preventive health education program for students in tertiary institutions in Southwest Nigeria. A cross-sectional study that was designed within the Knowledge, Attitudes, and Perception (KAP) model was used to collect information from 140 students. The age ranged from 17-32 years, with amean of 22.98 and SD ±3.14. The males constituted 61% of the respondents. Median age for the initiation and the regular use of drugs were 17 and 19 years. Almost all the students, 99% of them had been taught about drug abuse. However, 35% of them did not see drug abuse as a major problem in the society. Up to 37% of them believed that suffering health damage or medical problem due to drug abuse is not at all likely. The majority of the respondents (56%) believed that using drugs makes people cool, and 8% of the participants had experienced withdrawal symptoms. The majority of them knew that drug abuse could lead to mental illness (75%), violence, or aggressive outbursts under the influence of drugs (71%). The findings will help in developing a frame work for effective advocacy, policy formulation, and preventive health education program on substance abuse for students